Application of nursing project management for prolonging the indwelling time of peripheral intravenous indwelling needle in neonates (实施护理专案延长新生儿外周静脉留置针留置时间) - LIAO Ke (廖珂); YANG Li (杨莉); LAI Chunyan (赖春燕); ZHAO Lijuan (赵丽娟) (Journal of International Translational Medicine Limited, 2022)
Objective To explore the effect of nursing project management for prolonging the indwelling time of peripheral intravenous indwelling needle in neonates. Based on the analysis of potential problems such as catheter loss, phlebitis, liquid extravasation and tube blockage in the infusion treatment using peripheral venous indwelling needle, a nursing project management was carried out. Aiming at prolong the indwelling time to 72 hours, countermeasures from aspects of human, material, method and environment were analyzed and carried out, and usage of intravenous indwelling needle in neonates was systematically managed according to the standard procedure. Results The qualified rate of reaching target indwelling time increased from 33. 10% before implementation of nursing project management to 71. 56% after implementation of nursing project management. Conclusion The application of nursing project management can effectively prolong the indwelling time of peripheral intravenous indwelling needle in neonates, which is worthy of promotion in clinical practice. (目的 探讨运用护理专案延长新生儿外周静脉留置针留置时间的效果。方法 针对新生儿使用外周静脉留置针输液治疗中存在易脱落、静脉炎、液体外渗、堵管等问题, 科室积极开展护理专案活动, 以"外周静脉留置时间72小时"为目标留置时间, 从人、物、法、环四个方面进行分析并寻找对策, 对新生儿外周静脉留置针的使用进行了系统规范化管理。结果 目标留置时间合格率由护理专案活动前的33. 10%提高到71. 56%。结论 应用护理专案能有效延长新生儿外周静脉留置针的留置时间。)